Iwògbè ọkàn (self-conscience): a philosophical appraisal of human behaviors as viewed by òfún méji in ifá divination system (2022)
Humanity has grappled with different kinds of problems since antiquity ranging from natural disasters, sicknesses and diseases, famines and all sorts of problems. Unfortunately, a sizeable portion of human problems originates from fellow human beings, wars, civil unrests, frauds, corruption, rape and all sorts of evils. Nigeria, like other third world nation is bedeviled by its own array of problems given by its multi-religious and multi-cultural nature also made worse by the problem of bad leadership and mismanagement of public funds. The past decade has witnessed an unusual spike in killings and kidnapping, particularly in the menace of the Boko-Haram, Fulani herdsmen, other forms of insecurity, bad governance and blatant disregard for the rule of law. Nigeria is no doubt a religious nation. This realization makes it necessary to wonder if the populace especially the ruling class is still in possession of the individual guiding voice, judge or judgment known as conscience. Traditionally, philosophers, theologians and scientists view conscience as a unified faculty, from different perspectives, evidently this kind of conception is laden with tautologies because of the pluralistic and the subjective nature of the concept. This paper however, appraised the current realities in Nigeria especially in the area of human behaviours using the epistemic function of Iwògbè Ọkàn (self-conscience) as a philosophical tool through Òfún Méjì of the Ifá Divination System. This was done with a view to re-examining the issue of the degradation in human behaviours in order to know where Nigerians, using the Yorùbá of South-western Nigeria as a case study actually got it wrong. The study discovered that degradation in human behaviours in the contemporary Nigeria shows that the populace in spite of their obvious religiosity got it wrong because Ìwògbè Ọkàn is either lost or broken in the society. It is imperative therefore that Nigerians should make reexamination of themselves at the personal level a priority. The same way personal adjustments are made to appearance when a mirror is looked at, Ìwògbè Ọkàn should lead to changes at the individual and national level.